Solar exposure(s) and facial clinical signs of aging in Chinese women: impacts upon age perception - Flament F; Bazin R; Qiu H; Ye C; Laquieze S; Rubert V; Decroux A; Simonpietri E; Piot B (Dove Medical Press, 2015)
Frederic Flament,1 Roland Bazin,2 Huixia Qiu,3 Chengda Ye,3 Sabine Laquieze,4 Virginie Rubert,1 Aurelie Decroux,1 Elisa Simonpietri,5 Bertrand Piot1 1L'Oreal Research and Innovation, Paris, France; 2RB Consult, Bievres, France; 3L'Oreal Research and Innovation, Shanghai, People's Republic of China; 4Private Dermatology Consultancy, Montpellier, France; 5Biotherm International, Levallois-Perret, France Abstract: A new reference clinical atlas of facial signs dedicated to photoaging was applied to 301 Chinese women of various ages through standardized photographs. Such approach aimed at better describing the facial changes induced by both real/chronological age and sun exposure and their respective impact on two subcohorts of different behavior with regard to sun exposure. A total of 28 various facial signs were individually graded according to their severity by a panel of experts, and a perceived apparent age of each subject was assessed. Results showed that the severity of major signs significantly increased rather linearly with age, with a higher rate in sun-exposed subjects as compared with subjects who regularly avoid sun exposure. The severity of facial signs, all impacted by sun exposure, better correlated with perceived apparent age than real/chronological age. The protocol used in the present work, similar to that previously applied to two cohorts of French women, assigned a greater impact of sun exposure in the facial aging signs of Asian women – all clinical signs are influenced by extrinsic factors – as compared with Caucasian women of comparable ages, likely related to much more intense ultraviolet (UV) radiation. Keywords: photoaging, clinical evaluation, UV, perceived apparent age, solar exposure